Transpalpebral tonometry after penetrating keratoplasty - E.V. Karlova; A.V. Zolotarev; E.S. Milyudin; A.E. Pershakova (РМЖ "Клиническая офтальмология")
E.V. Karlova1, A.V. Zolotarev1,2, E.S. Milyudin1, A.E. Pershakova1 1T.I. Eroshevskiy Samara Regional Clinical Ophthalmological Hospital, Samara, Russian Federation 2Samara State Medical University, Samara, Russian Federation Aim: to assess the efficacy and safety of EASYTON transpalpebral intraocular pressure (IOP) tonometer in the early postoperative period after penetrating keratoplasty (PK). Patients and Methods: 43 patients after unilateral PK were enrolled. IOP measurements with palpation and EASYTON transpalpebral IOP tonometer in the operated eye were performed daily for 7 days. In addition, IOP measurements with palpation, EASYTON, and the Goldmann applanation tonometer (GAT) in the fellow (non-operated) eye were performed. Results: Bland-Altman plots demonstrated a rather high degree of the similarity of IOP measurements with palpation, GAT, and EASYTON in the non-operated eyes. Therefore, IOP measurement by palpation is a rather informative technique and can be used to compare the accuracy of EASYTON in the operated eyes of the same patients. During the second step, a high degree of the similarity of IOP measurements with palpation and EASYTON was demonstrated in the operated eyes after PK. Mean IOP spread (as demonstrated by three consecutive IOP measurements with EASYTON) was 1.32 mm Hg thus showing a high degree of repeatability. The lack of the nega tive effects of IOP measurements with EASYTON supports its safety. Conclusion: EASYTON transpalpebral IOP tonometer prevents the subjectivity of IOP measurements after PK and makes tonometry available to the general public. The lack of the contact with the cornea, a rather high accuracy, a high repeatability, and the lack of negative effects allow for using this device after PK. Keywords: transpalpebral IOP tonometer, intraocular pressure, penetrating keratoplasty, instrumental tonometry, EASYTON, non-contact tonometry. For citation: Karlova E.V., Zolotarev A.V., Milyudin E.S., Pershakova A.E. Transpalpebral tonometry after penetrating keratoplasty. Russian Journal of Clinical Ophthalmology. 2020;20(4):175–179. DOI: 10.32364/2311-7729-2020-20-4-175-179.